Downsides of Social Capital for Women During Disaster Recovery: Toward a More Critical Approach. (January 2013) - Ganapati, N. Emel
This article examines the downsides of social capital (networks of citizens) for women affected by disasters, an issue little understood in the public administration literature. Studying this issue is important due to women's unique vulnerabilities and resilience in the face of disasters. Based on the case study of the epicenter of the August 17, 1999, earthquake in Turkey (in-depth interviews, participatory site observation, a focus group, and review of secondary sources), this article suggests that despite its benefits, social capital has its downsides. It helps perpetuate gender-based assumptions and could put women in conflict with the state authorities.